2005
DOI: 10.1093/humrep/deh574
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward male fertility control: results of a multinational survey on four continents

Abstract: While MFC appears to be well accepted overall, the willingness to use this type of contraception varies widely between differing population groups. The specific characteristics and profile of any MFC product will have to be carefully evaluated to accurately assess its acceptance, both by men and their female partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
3
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(158 citation statements)
references
References 11 publications
5
143
3
7
Order By: Relevance
“…Brooks [12] found that 70% of respondents would not tolerate any side-effects, although their attitudes towards an effective male contraceptive were positive. Similar findings were reported by Weston et al [13] and Heinemann et al [23], in that any side-effects caused by methods of male contraception would not be desirable. More recently, in a mixed-method study in the East of England, Walker [27] explored attitudes towards the male pill and found that participants who were unwilling or undecided regarding MHC were more likely to be concerned about potential effects of the male pill on future fertility.…”
Section: Fear Of Side-effectssupporting
confidence: 87%
See 1 more Smart Citation
“…Brooks [12] found that 70% of respondents would not tolerate any side-effects, although their attitudes towards an effective male contraceptive were positive. Similar findings were reported by Weston et al [13] and Heinemann et al [23], in that any side-effects caused by methods of male contraception would not be desirable. More recently, in a mixed-method study in the East of England, Walker [27] explored attitudes towards the male pill and found that participants who were unwilling or undecided regarding MHC were more likely to be concerned about potential effects of the male pill on future fertility.…”
Section: Fear Of Side-effectssupporting
confidence: 87%
“…Even though both types of studies have yielded largely positive results regarding acceptability, attitudes towards the possibility of a male contraceptive pill seem to vary across research projects in various cultures, in line with the outcome of a multinational survey [23] which reported an average acceptance rate of 55%. Hence, although there is a majority in favour of MHC, it is somewhat slim and results are largely based on quantitative studies in relatively small sub-samples of cultures.…”
Section: Discussionmentioning
confidence: 73%
“…Men's opinions suggest that male hormonal contraceptives might be another possible choice. For couples that would choose it, this would demand the same share of use responsibility from the man´s side, as we encounter in female hormonal contraception (Heinemann, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Educational and income level, acceptance of vasectomy, and current use of contraception were important predictors of willingness to use a male hormonal contraceptive. 24 …”
Section: Ethnic Differences In Acceptability Of Male Contraceptive Mementioning
confidence: 99%